KANDUNGAN ZAT GIZI DAN DAYA TERIMA ES KRIM UBI JALAR UNGU PADA ANAK SEKOLA - Sari, Lina Novita; Purbowati; Mulyasari , Indri (JURNAL GIZI DAN KESEHATAN, 2019)
Background :Purple sweet potato can be processed into ice cream which has a lot of nutrients and is liked by school children. Objective: To analyzethe nutrient content and the acceptance of purple sweet potato ice cream in schoolchildren. Method :This research is a Pre Experimental Design research with One-shot Case Study. Sampling using Non Probability Sampling technique is as many as 75 school children. The research was carried out by making a variation of mixing the addition of purple sweet potato and milk on ice cream to then test the acceptability and test the nutrient content. Comparison of the results of the best received power between F1: F2: F3 is carried out using a hedonic scale test form. In F1 purple sweet potato ice cream, nutrient content was tested. Test the content of energy nutrients with the proximal method, protein by the Kjeldahl method, fiber with the ADF method, and anthocyanin substances by the Spectrophotometer method.Analysis using univariate Result :Nutrient content in purple sweet potato ice cream with F1 contains 263,698 kcal of energy, 1,176% / 100g of protein, 1,112% / 100g of fat, and 0,0130% / 100g of anthocyanin. Acceptance of school children is the best, namely on purple sweet potato ice cream with formula I, with a comparison of formula I: formula II: formula III = 81.3%: 72%: 61.3%. Conclusion: The content of energy, protein, and fiber in F1 purple sweet potato ice cream still does not meet the RDA, the requirement of healthy snacks to consume the daily needs of students is 30% energy and 23.3% protein. so it needs to consume other healthy snacks to meet the needs. The power to receive the best purple sweet potato ice cream is in F1 Abstrak : Latar belakang: Ubi ungu dapat diolah menjadi es krim yang banyak kandungan gizi dan disukai oleh anak-anak usia sekolah. Tujuan: Mengetahui kandungan zat gizi dan daya terima es krim ubi jalar ungu pada anak sekolah. Metode :Penelitian ini merupakan penelitian Pre Experimental Design dengan One-shot Case Study. Pengambilan sampel menggunakan teknik Non Probability Sampling yaitu sebanyak 75 anak sekolah. Penelitian yang dilakukan yaitu dengan membuat variasi pencampuran penambahan ubi jalar ungu dan susu pada es krim untuk kemudian diuji daya terima dan uji kandungan zat gizi. Dilakukan perbandingan dari hasil daya terima terbaik diantara F1 : F2 : F3 menggunakan form uji skala hedonic. Pada es krim ubi jalar ungu F1 dilakukan uji kandungan gizi. Uji kandungan zat gizi energi dengan metode proksimalt, protein dengan metode Kjeldahl, serat dengan metode ADF, dan zat antosianin dengan metode Spektrophotometer. Analisis data penelitian menggunakan univariat. Hasil: Kandungan zat gizi dalam es krim ubi jalar ungu dengan F1 mengandung energi 263,698 kkal, protein 1,176%/100g, lemak 1,112%/100g, dan antosianin 0,0130%/100g. Daya terima anak sekolah paling baik yaitu pada es krim ubi jalar ungu dengan formula I, dengan perbandingan formula I : formula II : formula III = 81,3% : 72% : 61,3%. Simpulan: Kandungan energi, protein, dan serat dalam es krim ubi jalar ungu F1 masih belum memenuhi AKG, syarat makanan jajanan sehat terhadap konsumsi kebutuhan sehari siswa sebesar 30% energi dan 23.3% protein. sehingga perlu konsumsi jajanan sehat yang lain untuk memenuhi kebutuhan. Daya terima es krim ubi jalar ungu paling baik adalah pada F1.